AN ANALYSIS OF MORAL VALUES IN THE MALEFICENT : “MISTRESS OF EVIL” MOVIE - Sinaga, Juwita Boneka (English Department, University of Riau Kepulauan, Batam,Indonesia, 2023)
Abstract The objective of this research is to find out the kinds of moral values in Maleficent: